1995
DOI: 10.1051/lait:19954-524
|View full text |Cite
|
Sign up to set email alerts
|

Protein degradation and amino acid metabolism by propionibacteria

Abstract: Summary-This article reports the existing knowledge about the proteolytic system of Propionibacterium and its ability to degrade amino acids. Propionibacterium contains at least 2 weak proteinases, 1 cell wall-associated and 1 intracellular or membrane-bound. A wide variety of peptidases, such as amino peptidases, proline iminopeptidase, proline imidopeptidase, X-prolyl-dipeptidyl-aminopeptldase, endopeptidases and carboxypeptidase, has been described and characterized. A wide variety of amino acids, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…and characterized. Amino acids, especially aspartic acid, alanine, serine and glycine, are degraded by Propionibacterium, with variations among species and strain [47]. On the other side, cutaneous propionibacteria, have the ability to hydrolyze different proteins, like gelatin and fibronectin, and to promote damages and inflammation of the host tissues.…”
Section: Main Physiological Characteristics Of Propionibacteriummentioning
confidence: 99%
“…and characterized. Amino acids, especially aspartic acid, alanine, serine and glycine, are degraded by Propionibacterium, with variations among species and strain [47]. On the other side, cutaneous propionibacteria, have the ability to hydrolyze different proteins, like gelatin and fibronectin, and to promote damages and inflammation of the host tissues.…”
Section: Main Physiological Characteristics Of Propionibacteriummentioning
confidence: 99%
“…The contribution of each of these flora to proteolysis remains unclear, and their proteolytic systems are incompletely described. PAB proteinases are weakly implicated in the breakdown of caseins [20]. Nevertheless, PAB possess nu-merous intracellular peptidases active on casein peptides [15].…”
Section: Introductionmentioning
confidence: 99%
“…PAB possess proteolytic enzymes [57]; however, most of them are intracellular and are poorly released within the cheese. Fröhlich-Wyder et al [32] proposed that proteolysis and amino acid catabolism may result in a higher pH, and thus better growing conditions for the PAB, and hence a greater gas production.…”
Section: Interactions Between Startersmentioning
confidence: 99%
“…Martley and Crow [71] demonstrated that citrate metabolism can occur in Swiss-type cheese resulting in the complete utilisation of the citrate; it was suggested that non-starter Cit + lactobacilli may be responsible. Certain pathways of amino acid degradation can result in CO 2 production [57]; decarboxylation of amino acids results in the liberation of CO 2 and the conversion of amino acids to amines [17]. For example, decarboxylation of glutamic acid to γ-aminobutyric acid by mixed strains of thermophilic cultures is the main source of CO 2 in some Gouda-type cheeses [123].…”
Section: Other Sources Of Gasmentioning
confidence: 99%